1997 ILRI project work plans - International Livestock Research Institute (International Livestock Research Institute, 1997)
The six programmes at ILRI are discussed in this Report. The first part deals with the conservation of Biodiversity programme where characterisation and conservation of indigenous animal as well as forage genetic resources are discussed. This part is followed by presentations of the five programmes, viz. Production Systems Research Programme, Utilization of Tropical Feed Resources Programme, Animal Health Improvement Programme, Livestock Policy analysis Programme and Strengthening Collaboration with NARS. Each programme has two, twenty, five, seven, five and six projects respectively. Under each project is outlined the proejct title, location, scientists and associates involved, collaborating institutions, background and justification, objectives, work plan for 1997, expected outputs and publications produced.